Juvenile development and growth patterns in the mud crab Eurytium limosum (Say, 1818) (Decapoda, Brachyura, Xanthidae) under laboratory conditions - Guimaraes, F. J.; Negreiros-Fransozo, M. L. (Taylor & Francis Ltd, 2005)
The post-larval development of the mud crab Eurytium limosum was studied under laboratory conditions by using the offspring of ovigerous females collected at the Comprido River mangrove, SP, Brazil. The first crab stage is fully described and the juvenile development, until crab stage 10, is examined with emphasis on morphological change, sexual differentiation and growth patterns. The carapace of the first crab stage is nearly square as observed in other xanthids, becoming similar to adults only at stage 15. The sexes can be distinguished from stage four, based on the number of pleopods and their morphology. While the intermoult period increases, the moult percentage decreases at each stage. The abdominal allometric growth is sex-dependent, with males showing a negative (b=0.71) and females an isometric (b=0.95) relative growth pattern. Male gonopods undergo a positive allometric growth, and their shape changes remarkably until sexual maturity. The cheliped dentition can be observed after stage 4. Regardless of sex, most crabs have a molariform right cheliped, which is thought to aid the handling of asymmetric prey such as gastropods.
Keywords: Decapoda; Eurytium limosum; juvenile development; morphology; relative growth; Xanthidae